Pengaruh Karakteristik Pekerjaan dan Karakteristik Organisasi terhadap Kepuasan Kerja Pegawai pada Puskesmas Kecamatan Sumbermanjing Wetan di Malang - Heri Sudarsono (Jurnal Aplikasi Manajemen, 2012)
The objective of research seems: (1) to examine whether the variable of occupational and organizational characteristics simultaneously (collectively) have the significant effect on the work satisfaction among the employee of Public Health Center at Sumbermanjing Wetan Subdistrict, Malang; and (2) to understand the variable of occupational and organizational characteristics partially (individually) have the significant effect on the work satisfaction among the employee of Public Health Center at Sumbermanjing Wetan Subdistrict, Malang. Research type subsumes into explanatory research including the population of the employee of Public Health Center at Sumbermanjing Wetan Subdistrict, Malang. Sampling technique considers Probability Sampling in which the sample counts to 40 respondents. The analysis tool uses Multiple Regression while F-test and t-test ascertain the significance facilitated by SPSS software. Results of simultaneous analysis (F-test) indicate that the variables of occupational characteristic (X1) and organizational characteristic (X2) have significant effect on the work satisfaction among the employee with significance F rate (0.000) smaller than alpha of 0.05. Meanwhile, partial analysis (t-test) shows that the variables of occupational characteristic (X1) and organizational characteristic (X-2) have significant effect on the work satisfaction of employee, seeing the occupational characteristic of 0.40 and organizational characteristic of 0.012 smaller than alpha of 0.05.Keywords: Occupational Characteristic, Organizational Characteristic, Work Satisfaction